2011
DOI: 10.1021/es202400s
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of Chlorothalonil Fungicide on Plant Leaf Models

Abstract: Photodegradation is seldom considered at the surface of vegetation after crop spraying. Chlorothalonil, a broad-spectrum foliar fungicide with a very widespread use worldwide, was considered. To represent the waxy upper layer of leaves, tests were performed within thin paraffin wax films or in n-heptane. Laser flash photolysis together with steady-state irradiation in n-heptane allowed the determination of the photodegradation mechanisms Chlorothalonil ability to produce singlet oxygen was measured; noteworthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 42 publications
2
56
0
4
Order By: Relevance
“…142) The LFP study with quenching by 3 O 2 showed T* as a key intermediate in the photolysis of chlorothalonil, and reductive dechlorination was the main reaction in water. 27,28) Photosubstitution seems more favorable in the aqueous photolysis of pesticides that have a chlorinated aryloxy moiety. Phenoxyacetic herbicides, such as 2,4-D, 143) 2,4,5-T, 113) and triclopyr, 144) generally produced the corresponding 2-OH derivatives; however, reductive dechlorination at the 4-position was more favorable for dichlorprop.…”
Section: Dehalogenation 3151 Dechlorinationmentioning
confidence: 99%
“…142) The LFP study with quenching by 3 O 2 showed T* as a key intermediate in the photolysis of chlorothalonil, and reductive dechlorination was the main reaction in water. 27,28) Photosubstitution seems more favorable in the aqueous photolysis of pesticides that have a chlorinated aryloxy moiety. Phenoxyacetic herbicides, such as 2,4-D, 143) 2,4,5-T, 113) and triclopyr, 144) generally produced the corresponding 2-OH derivatives; however, reductive dechlorination at the 4-position was more favorable for dichlorprop.…”
Section: Dehalogenation 3151 Dechlorinationmentioning
confidence: 99%
“…The field-extrapolated half-life of chlorothalonil due to photolysis was estimated at 5.3 days (Monadjemi et al, 2011). Lichiheb et al (2014) estimated photodegradation of chlorothalonil at 31.1% after 5 days.…”
Section: Experimental Modelmentioning
confidence: 99%
“…However in field trial on potato the fate of chlorothalonil due to volatilization was only 5% after 7.6 days (Leistra & Van Den Berg, 2007). Furthermore, Monadjemi et al (2011) estimated half-life of chlorothalonil due to photodegradation at 5.3 days. There are studies indicating high azoxystrobin stability on tomato leaves within 1-4 days after spraying (Szpyrka & Sadło, 2008) and even after 7-10 days on fruits (Garau et al, 2002).…”
mentioning
confidence: 91%
“…Chlorothalonil, exposed directly to light (300-400nm) photolytically degraded more rapidly in natural waters (DT 50 = 0.21-0.76 d) than in a buffered aqueous system (pH 7; DT 50 = 1.1d; Wallace et al 2010). Monadjemi et al (2011) investigated the photodegradation of chlorothalonil on a simulated plant surface, specifically using paraffin wax (irradiated at wavelengths between 300-800nm). A field-extrapolated half-life of 5.3 d resulted, and suggested that chlorothalonil is susceptible to direct photolysis, in addition to surface penetration.…”
Section: Photolysismentioning
confidence: 99%
“…A field-extrapolated half-life of 5.3 d resulted, and suggested that chlorothalonil is susceptible to direct photolysis, in addition to surface penetration. In addition, these authors found the main degradation route was via reductive dechlorination (Monadjemi et al 2011). Waltz et al (2002) studied the photodegradation of hydroxychlorothalonil (HC), chlorothalonil's major hydrolytic metabolite.…”
Section: Photolysismentioning
confidence: 99%